2021
DOI: 10.2147/ott.s268056
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Regulates the Apoptosis of Human Megakaryocyte Cells via NF-κB/IL-17 Signaling

Abstract: Objective: To investigate the role of Helicobacter pylori (HP) on the regulation of NF-κB/ IL-17 signaling, mechanisms underlying apoptosis in human megakaryocyte cell lines Dami. Methods: Firstly, the mouse model of immune thrombocytopenia (ITP) was established. Then, the mice were subjected to gastric perfusion with HP. Next, the changes in platelet and bone marrow megakaryocyte classification were assessed in each group. Human megakaryocyte Dami cells were treated with HP in vitro for 3, 6, or 9 h; and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…A meta-analysis of six studies involving 241 patients proved that H. pylori eradication is an effective treatment for ITP patients ( Kim B. J. et al, 2018 ). Lei et al (2021) reported that H. pylori can promote platelet destruction in mice, and the mechanisms may be related to activating NF-κB/IL-17 signaling.…”
Section: Blood System Diseasementioning
confidence: 99%
“…A meta-analysis of six studies involving 241 patients proved that H. pylori eradication is an effective treatment for ITP patients ( Kim B. J. et al, 2018 ). Lei et al (2021) reported that H. pylori can promote platelet destruction in mice, and the mechanisms may be related to activating NF-κB/IL-17 signaling.…”
Section: Blood System Diseasementioning
confidence: 99%
“…1D ). IL-17 signaling promotes apoptosis of human megakaryocyte cells, and neutralization of IL-17 up-regulates anti-apoptotic Bcl-2 protein in megakaryocyte cells [ 14 ]. Moreover, IL-17 exacerbates hepatic inflammation through regulatory T cell-mediated responses in a mouse model of NAFLD [ 9 ].…”
mentioning
confidence: 99%